International Handbook of Teacher Quality and Policy 2017
DOI: 10.4324/9781315710068-17
|View full text |Cite
|
Sign up to set email alerts
|

Assumptions and Implications of Adopting Educational Ideas from the West

Abstract: You will be contacted as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In Turkey, being able to apply a formula and get the correct answer to questions is necessary and sufficient for success in both classroom assessments and in high-stakes tests. Such tests are highly competitive, and parents perceive students' performance in them to be very important (Altinyelken & Sozeri, 2017) as the results determine which high school or university a student will go to. To be placed in relatively good schools and universities, students work very hard; they practice hundreds of questions either at the school in mathematics classes, or during out-of-school instruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, being able to apply a formula and get the correct answer to questions is necessary and sufficient for success in both classroom assessments and in high-stakes tests. Such tests are highly competitive, and parents perceive students' performance in them to be very important (Altinyelken & Sozeri, 2017) as the results determine which high school or university a student will go to. To be placed in relatively good schools and universities, students work very hard; they practice hundreds of questions either at the school in mathematics classes, or during out-of-school instruction.…”
Section: Discussionmentioning
confidence: 99%
“…The Turkish curriculum suggests teachers use appropriate manipulatives and technology where applicable, leaving it as optional, as Erbilgin (2017) presumed, because those resources might not be available in all schools. Several studies from Turkey (Altinyelken, 2011;Altinyelken & Sozeri, 2017) have reported that a teacher's decision to incorporate particular curriculum aspects (in this case, the use of mathematical tools, including both representational and physical) into their classroom practice is influenced by several dimensions in education, including their beliefs, interpretations of the pedagogical approaches, and classroom realities (Altinyelken & Sozeri, 2017) as well as the prevalence of national high-stakes testing (Ozpolat, 2013). In the absence of observational or interview data, it is difficult to confirm that the curriculum guidance or availability of materials, or exams and the examination system, have influenced the student response patterns found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This result may also be associated with another result of the study which was teachers believed their opinions were not taken into consideration during curriculum change. As also Koşar-Altınyelken and Sözeri (2017) and Saracaloğlu et al (2010) found, teachers' needs and voices were not considered sufficiently in the curriculum development process and teachers felt disappointed to see that their feedback were hardly reflected in curriculum change and their views had little impact on the process. Thus, it is suggested that teachers' opinions should be sought during curriculum development and curriculum change processes since problems may arise if teachers are disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…(European Schoolnet, 2018). Research suggests that community (parents, schools) expectations in relation to these kinds of examinations influence teachers' instructional practices (Altinyelken, 2011;Altinyelken & Sozeri, 2017) and subsequently their MKT. For example, if the examination focuses on symbolic manipulation and procedural techniques as opposed to concepts associated with functions, then teachers are likely to privilege the former.…”
Section: Discussion and Concluding Commentsmentioning
confidence: 99%